Observation of a Fano Resonance at 92 meV (13.5 µm) in Al0.2Ga0.8N/GaN-Based Quantum Cascade Emitters - Daniel Hofstetter; Andreas D. Wieck; Hans Beck; David P. Bour (Micromachines, 2025)
We report on asymmetrically shaped Fano resonances in Al0.2Ga0.8N/GaN-based quantum cascade structures. In order to observe this type of resonance in electro-luminescence, a spectrally narrow feature must interact with a broad, quasi-continuous emission. While the narrow waveform is provided by the GaN-based LO-phonon at 92 meV (13.5 µm, 741 cm−1), the broad peak consists of overlapping inter-subband transitions between several higher-order excited states ranging from 80 to 300 meV and the ground state. Through the interference of these spectrally dissimilar peaks, a typical, asymmetric Fano line shape is generated.